Comparación morfométrica entre machos y hembras de Cachama Negra (Colossoma macropomum, Cuvier 1818) mantenidos en estanque (2004)
ABSTRACT: The Cachama Negra (Colossoma macropomum, Cuvier 1818) does not display sexual dimorphism, and its sex is only recognized when they reach the sexual maturity after three years old. To sex them before their first sexual maturity would be of great importance in aquaculture in order to decrease cost and focus on females, which have a major reproductive value. The aim of this study was to look for associations among the sex and some external morphometric features that will allow the females recognition. 46 adults, (12 males and 34 females), were studied in the Universidad de Antioquia fishery station. 29 phenotypic features were measured with a vernier caliper (0.001 mm), and the Standard Length with a conventional ichthyometer (0.1 mm). The Mann-Whitney test does not find significant differences (p>0.05) on each variable between male and female, confirming the features absence of sexual dimorphism. The descriptive analysis showed a greater trend of averages, standard deviations and variation coefficient on males, pointed out a homogeneity on females. The Spearman correlation test showed a general correlation among all variables (p<0.01). The Principal Component Analysis does not showed significant differences between male and female on the first component (CP1), but some differences were found in the others (CP2 and CP3), that pointed out informative variables on head zone in males and belly finbase in females. This association among the sex and external morphological features in this group makes possible a follow up of these traits from juveniles to adulthood to be considered such early selection markers.